Prediction Fruitfulness of the Bina Mina Village Unit Cooperative (KUD) in Labuhan Maringgai District, East Lampung Regency - Annisa Elvaretta Insani; Dyah Aring Hepiana Lestari; Maya Riantini (Departement of Socio-Economic Agricuture, Faculty of Agriculture, 2021)
The Bina Mina Village Unit Cooperative is an active cooperative in East Lampung Regency that was founded in 1975, but it has never been evaluated as successful using a tripartite approach, therefore the cooperative has no idea how successful its management. The goal of this research is to examine cooperative success from three perspectives (tripartite), namely cooperative success as a corporate entity, cooperative success in contributing to development, and cooperative success in delivering community benefits. The study employed a case study approach, which included direct interviews with five cooperative administrators and the completion of a questionnaire. The information was quantitatively examined using the 2015 Cooperative Rating Guidelines, which included five areas of cooperative institutions: business, finance, community benefits, and member benefits. The findings of this study show that cooperatives are successful as well-qualified commercial entities, contribute to well-qualified development, and provide benefits to non-qualified members.